Asymmetric first‐order transition and interlocked particle state in magnetocaloric La(Fe, Si)13. Issue 2 (7th January 2015) - Waske, Anja; Giebeler, Lars; Weise, Bruno; Funk, Alexander; Hinterstein, Manuel; Herklotz, Markus; Skokov, Konstantin; Fähler, Sebastian; Gutfleisch, Oliver; Eckert, Jürgen
<x xml:space="preserve">Abstract</x> In‐situ synchrotron XRD measurements of the magnetocaloric material LaFe11.8Si1.2 are used to understand virgin effects and asymmetry of the underlying first order magnetovolume transition. A remarkable change of the transition kinetics occurs after the first cycle, which we attribute to the formation of cracks originating from the volume change. Tomographic imaging revealed that the bulk material disintegrates via an interlocked state where fragments are loosely connected. Though cracks have opened between the fragments, the transition is sharp, which we attribute to magnetostatic interactions. In the cycled sample we find a strong asymmetry between the transition interval upon heating and cooling, which we explain by isostatic pressure acting on parts of the sample during the cooling transition. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)